MODEL PENDIDIKAN KARAKTER DI PERGURUAN TINGGI AGAMA ISLAM (Studi tentang Pendidikan Karakter Berbasis Ulul albab di Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Muhammad Walid (El-QUDWAH, 2011)
UIN Maliki  Malang  is  one  kind  of  Islamic  University  having  concern  and attention much to the formation of student character. This is marked by the spirit of UIN Maliki trying to deliver alumnus, having spiritual depth, big character, knowledge comprehensiveness,  and  professional  ripeness.  Those  four  concepts  actually  was appropriate with the grand design of character education developed by Kemendiknas, that is the growing of cognitive aspect, affective, conative, and psychomotoric. Those four concepts  of UIN Maliki can also be grouped character education configuration into totality context of psychology process and social-cultural, they are: Spiritual and emotional development, intellectual development, Physical and kinestetic development, and Affective and Creativity development. The model of character education developed by UIN Maliki Malang create ulul albab frame as the basic. Inside of developing the students character, UIN Maliki Malang base on value of the existence of UIN and the vision, mission of the university. Theoritic base that is used as handle in developing character education ulul albab base is Islamic conception. The aim of character education based on ulul albab UIN Maliki Malang are: (1) shaping muslim having ulul albab values; (2) those values are religious, patient, sincere, tawakkal, tawadlu’, istiqamah, surrender, fair, honesty, soft hearted, high spirit, criticize, boarder education, can see natural and social phenomenon appropriately, caring, emphaty, tolerant, cooperation, professional; (3) becoming basic base inhabited all the implementation and academic activity in UIN Maliki Malang. There are night characters taking from ulul albab basic, they are: (1) Religius (patient, sincere, tawakkal, tawadlu’, istiqamah, surrender, fair, honesty, soft hearted, high spirit); (2) criticize (they like to ask) (3) having boarder knowledge; (4) can see natural and social phenomenon appropriately (smart); (5) caring  others;  (6)  emphaty;  (7)  Tolerant;  (8)  cooporation;  (9)  Professional.  Those nights characters be reduced again into five values developed in UIN Maliki Malang, they are: Jihad, Creatif, Inovative, Critis, Religius, Excellence and Smart shortly with J-CRES. The method used in shaping characters J-CRES ulul albab base through: (1) the education program  blending pesantren and university; (2) Tarbiyah Ulul Albab lecturing; (3) Intrakurikuler, kokurikuler dan ekstrakulikuler activities.